Metronidazole-induced Encephalopathy. (2019) - Phyu, Htay; Edmond, Michael B.; Kobayashi, Takaaki
Abstract: Metronidazole is commonly used in the treatment of anaerobic infections. While neuropathy is known to be associated with metronidazole, encephalopathy has been rarely reported. We herein present a case of metronidazole-induced encephalopathy presenting as frequent falls and slurred speech. Magnetic resonance imaging of the brain demonstrated T2/FLAIR hyperintensity in the dentate nuclei bilaterally. Soon after the discontinuation of metronidazole, dysarthria and dysmetria resolved. Metronidazole-induced encephalopathy should be considered in patients presenting with new neurologic symptoms after the initiation of metronidazole.